Orientación de los servicios microfinancieros hacia los más pobres - Carola Conde Bonfil (El Colegio Mexiquense, A.C., 2005)
One of the most important discussions in current micro-finance theory is whether it is necessary or counter-productive to focus micro-financial services to the poorest. In this document, we describe the most well known methodologies. We conclude that focussing in specific groups restricts the access to others that are considered non-vulnerable. As a result, the so-called inclusion error is corrected, but the possibilities of increasing the exclusion error are greater since the methodologies that guide the programmes have been designed to detect the poorest within 70-80%. Moreover, there is the risk of destroying the existing social capital in the communities where microfinancial projects operate.